Determining the Zero-Field Cooling/Field Cooling Blocking Temperature from Ac Susceptibility Data for Single-Molecule Magnets - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2025)
We present a general relationship between the magnetisation blocking temperature (TB) measured using the zero-field cooling/field cooling technique (ZFC/FC) and the temperature-dependent spin relaxation time obtained from AC susceptibility and magnetisation decay measurements. The presented mathematical approach supplies ZFC/FC blocking temperatures at any heating rate (RH), providing comparable values to those obtained experimentally, as demonstrated by testing 107 examples for reported single-molecule magnets (SMMs) where the ZFC/FC curve has been measured. This procedure is examined in further detail for a new single-molecule magnet, [Dy(OPAd2Bz)2(H2O)4Br]Br2·4THF (1) (OPAd2Bz: di(1-adamantyl)benzylphosphine oxide). For this compound, ZFC/FC measurements were made over a broad range of heating rates (0.01-5 K min−1), which agreed with the general behaviour predicted from AC susceptibility data. We discuss how the demagnetisation mechanism determines the sensitivity of TB with respect to the heating rate: TB is mostly insensitive to RH for Orbach relaxation, while there is a larger sensitivity for Raman-limited systems. Our conclusions provide a clear physical interpretation of ZFC/FC blocking temperatures, aiding in the proper contextualization of this figure of merit. © 2025 The Royal Society of Chemistry.